The Role of Teachers and Student Parents in Online Learning Times Covid-19 - Fandi H. Binggo (Newinera Publisher, 2022)
This study aims to determine the role of teachers and parents in online learning in the Covid-19 situation of Class VI SD Laboratorium UNG. This research is a descriptive qualitative method by using case study research, and the sample was taken by stratified random sampling with number of samples was 20 respondents. The process of collecting data was done through observation, interviews, questionnaires and documentation. The results of the study show the role of teachers and parents in online learning during the Covid-19 situation has a very important influence. The role of teacher as a motivator, innovator and evaluator during online learning in the COVID-19 pandemic situation. The role of parents in supporting online learning by providing facilities, accompanying and directly supervising their children during the learning process at home. Online learning makes parents closer, knowing the character and learning outcomes of students